Effectiveness of Distraction Techniques for Pain Management During Dental Anesthesia in Pediatric Procedures - Bardales Martínez, María José (2025)
To compare the effectiveness of distraction techniques in pain management during the administration of dental anesthesia in pediatric procedures. This observational, longitudinal, and descriptive study included a sample of 64 pediatric patients: 36 females (56.25%) and 28 males (43.75%), with an average age of 7.3±1.5 years. The participants were divided into two groups: one using audiovisual distraction (32 patients) and the other using audio distraction (32 patients). Pain levels were assessed using the Wong-Baker scale before and after the procedure, and the SEM scale during the procedure. Based on the SEM scale, no statistically significant differences were observed between the two techniques during the procedure (p>0.05), indicating equal effectiveness. Similarly, the Wong-Baker scale showed no statistically significant differences (p>0.05) in pain perception after the procedure between the two techniques. Both audiovisual and audio distraction techniques are effective for pain management during the administration of dental anesthesia in pediatric patients.